Implementation of Waqf Asset Management Strategy by the Waqf Management Agency (BPW) of the Ar Risalah Foundation, Padang City - Nisa', Annisa Suryani Oktapia; Wira, Ahmad; Afriyani, Maisyah; Sepriandi, Rizki Jummi (LP2M IAIN Palopo, 2025)
This study aims to analyze the waqf asset management strategy used by the Ar-Risalah BPW in Padang City. This study aims to evaluate the waqf asset management strategy implemented by the Ar-Risalah Waqf Management Agency (BPW) in Padang City. The main focus of this study is on how the strategy is implemented by the Ar-Risalah Foundation BPW. Data were collected through interviews with the administrators and nazhir of the Ar-Risalah BPW, waqf asset managers in the field, and guardians of the Ar-Risalah Foundation, supported by documentation in the form of the 2020–2024 Ar-Risalah BPW financial report. In addition, this study also refers to literature such as books, scientific journals, and the results of relevant previous studies. The results of the study show that the waqf management strategy by the Ar-Risalah Foundation BPW includes three main aspects: collection, management, and distribution of waqf. In the collection stage, BPW utilizes digital technology and collaborates with various institutions, as well as increasing public education regarding productive waqf. Asset management is carried out optimally through training for managers, periodic evaluations, and the use of technology to increase efficiency. Meanwhile, the distribution of waqf benefits covers the education and economic empowerment sectors, with a transparent system and monitoring mechanism to ensure positive and sustainable impacts. Keywords: